Radioprotective Potential of Sulindac Sulfide to Prevent DNA Damage Due to Ionizing Radiation - Torabizadeh SA; Rezaeifar M; Jomehzadeh A; Nabizadeh Haghighi F; Ansari M (Dove Medical Press, 2019)
Seyedeh Atekeh Torabizadeh,1 Mehdi Rezaeifar,1 Ali Jomehzadeh,2 Farzaneh Nabizadeh Haghighi,1 Mehdi Ansari3 1Pharmaceutics Research Center, Institute of Neuropharmacology, Kerman University of Medical Sciences, Kerman, Iran; 2Department of Medical Physics, Faculty of Medicine, Medical Physics Department, Radiotherapy & Oncology Unit, Shafa Kerman Hospital, Kerman University of Medical Sciences, Kerman, Iran; 3Drug and Food Control Department, Kerman University of Medical Sciences, Kerman, IranCorrespondence: Seyedeh Atekeh TorabizadehPharmaceutics Research Center, Institute of Neuropharmacology, Kerman University of Medical Sciences, Kerman, IranTel +989132914643Fax +983431325215Email a.torabi@kmu.ac.irIntroduction: The ionizing radiation exposure of the normal cell causes damage to DNA, which leads to cell dysfunction or even cell death. However, it is necessary to identify new radio protectives in order to protect normal cells. Sulindac sulfide (SS) is a metabolite of sulindac (a non-steroidal anti-inflammatory drug) known as a cyclooxygenase inhibitor. Free radicals and reactive oxygen species are generated in the IR-exposed cells. Also, the induced inflammation process causes damage in DNA.Purpose: In this research, the radioprotective effect of SS was investigated against genotoxicity and lipid peroxidation induced by ionizing radiation in the human blood lymphocytes.Methods: In this study, the human blood samples were pretreated with SS at different concentrations (10, 25, 50, 100 and 250 μM) and then were exposed to IR at a dose of 1.5 Gy. The micronucleus (MN) assay was used to indicate the radioprotective effects of SS on exposed cells. Total antioxidant activity of the SS was measured by using FRAP and DPPH assay. Also, the malondialdehyde (MDA) levels and the activity of superoxide dismutase (SOD) on the exposed cells were evaluated.Results: It was found that SS decreased the percentage of MN induced by IR in exposed cells. Maximum reduction in the frequency of MN was observed at 250 μM of SS (87%) that provides the highest degree of protection against IR. On the other hand, pretreatment at 250 μM of SS inhibited IR-induced oxidative stress, which led to a decrease in the MN frequencies and MDA levels, while SOD activity showed an increase in the exposed cells.Conclusion: It could be concluded that SS as a good radioprotective agent protects the human normal cells against the oxidative stress and genetic damage induced by IR.Keywords: sulindac sulfide, DNA damage, MN, radioprotective, genotoxicity, lipid peroxidation